Musculoskeletal images classification for detection of fractures using transfer learning - Kandel, Ibrahem (2021)
Kandel, I., Castelli, M., & Popovič, A. (2020). Musculoskeletal images classification for detection of fractures using transfer learning. Journal of Imaging, 6(11), 1-14. [127]. https://doi.org/10.3390/jimaging6110127